Development of entrepreneurial capabilities: Use of the Role Model (AACINI - International Journal of Industrial Engineering, 2020)
This work presents planned activities that are developed within the subject Introducción a la Ingeniería Industrial of the Ingeniería Industrial career of the Facultad de Ciencias Agrarias of the Universidad Nacional del Nordeste for the development of entrepreneurial skills in their students. These activities aim to achieve awareness, the development of values and the strengthening of personal skills that allow the student to assess, acquire, implement, reinforce and consolidate skills and abilities related to entrepreneurial skills. To this end, students visit recognized companies of our company, in such a way that the student has an approximation to the reality of the business world through these visits and interviewing entrepreneurs.
Keywords: Role Model; Entrepreneurial Competences; Local Development